Histopathological tumor invasion of the mesenterico-portal vein is characterized by aggressive biology and stromal fibroblast activation. Issue 1 (January 2017) - Lapshyn, Hryhoriy; Bolm, Louisa; Kohler, Ilona; Werner, Martin; Billmann, Franck G.; Bausch, Dirk; Hopt, Ulrich T.; Makowiec, Frank; Wittel, Uwe A.; Keck, Tobias; Bronsert, Peter; Wellner, Ulrich F.
Abstract: Background: Mesenterico-portal vein resection (PVR) during pancreatoduodenectomy for pancreatic head cancer was established in the 1990s and can be considered a routine procedure in specialized centers today. True histopathologic portal vein invasion is predictive of poor prognosis. The aim of this study was to examine the relationship between mesenterico-portal venous tumor infiltration (PVI) and features of aggressive tumor biology. Methods: Patients receiving PVR for pancreatic ductal adenocarcinoma of the pancreatic head were identified from a prospectively maintained database. Immunohistochemical staining of tumor tissue was performed for the markers of epithelial–mesenchymal transition (EMT) E-Cadherin, Vimentin and beta-Catenin. Morphology of cancer-associated fibroblasts (CAFs) was assessed as inactive or activated. Statistical calculations were performed with MedCalc software. Results: In total, 41 patients could be included. Median overall survival was 25 months. PVI was found in 17 patients (41%) and was significantly associated with loss of membranous E-Cadherin in tumor buds (p = 0.020), increased Vimentin expression (p = 0.03), activated CAF morphology (p = 0.046) and margin positive resection (p = 0.005). Conclusion: Our findings suggest that PVI is associated with aggressive tumor biology and disseminated growth less amenable to margin-negative resection.